SISTEM INFORMASI PEMESANAN LILINBERBASIS WEB (Information Technology and Telematics, 2013)
Abstract : Kwan Sing Bio temple is one of the largest place of   worship in the city of Semarang. Any information  that you want to search about Kwan Sing Bio  Temple in Semarang only  by  phone  or  speech   community.   This  makes  the introduction of Kwan  Sing Bio   temple in Semarang. The research  problem  is ordering candles in temple Kwan Sing Bio Semarang are still in a certain range. This study aims to extend the reservation  candles on Kwan Sing Bio temple in Semarang, so  the people who want to put a light or candle in the temple of Kwan Sing Bio Semarang can do it online.  Analytical tools used are DFD (Data  Flow   Diagram)  and  ERD.  The  software  used  is Dreamweaver MX. Analysis and design results are expected to  help and  provide  convenience  for  customers  ordering  candles. And simplify the management of candle orders. Candle booking website is intended as a form offers convenience  for  customers.  With  the  online  booking  these customers no longer need to ask the details of each product and to place an order candle wax easily.     Keywords Reservations, candles, KwanSingBio Temple